Proof-of-concept for effective antiviral activity of an in silico designed decoy synthetic mRNA against SARS-CoV-2 in the Vero E6 cell-based infection model - Atari, Nofar; Erster, Oran; Shteinberg, Yair Heskiau; Asraf, Hadar; Giat, Eitan; Mandelboim, Michal; Goldstein, Itamar (Frontiers in Microbiology, 2023)
The positive-sense single-stranded (ss) RNA viruses of the Betacoronavirus (beta-CoV) genus can spillover from mammals to humans and are an ongoing threat to global health and commerce, as demonstrated by the current zoonotic pandemic of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Current anti-viral strategies focus on vaccination or targeting key viral proteins with antibodies and drugs. However, the ongoing evolution of new variants that evade vaccination or may become drug-resistant is a major challenge. Thus, antiviral compounds that circumvent these obstacles are needed. Here we describe an innovative antiviral modality based on in silico designed fully synthetic mRNA that is replication incompetent in uninfected cells (termed herein PSCT: parasitic anti-SARS-CoV-2 transcript). The PSCT sequence was engineered to include key untranslated cis-acting regulatory RNA elements of the SARS-CoV-2 genome, so as to effectively compete for replication and packaging with the standard viral genome. Using the Vero E6 cell-culture based SARS-CoV-2 infection model, we determined that the intracellular delivery of liposome-encapsulated PSCT at 1 hour post infection significantly reduced intercellular SARS-CoV-2 replication and release into the extracellular milieu as compared to mock treatment. In summary, our findings are a proof-of-concept for the therapeutic feasibility of in-silico designed mRNA compounds formulated to hinder the replication and packaging of ssRNA viruses sharing a comparable genomic-structure with beta-CoVs.